ANALISIS REKRUTMEN DAN KADERISASI PARTAI POLITIK PADA FENOMENA CALON TUNGGAL PETAHANA STUDI KASUS : PILKADA KABUPATEN PATI 2017 - Danny Widodo Uji Prakoso; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
This study discusses the phenomenon of Regional Head Election (Pilkada) in Pati District in 2017 which is very interesting to be studied because it is only followed by one pair of candidates who have to compete with empty boxes. This phenomenon can be attributed to the procession of recruitment and recruitment of political parties in Pati Regency because 8 of 9 political parties prefer to carry one candidate, while one other party can not carry the candidate because the number of seats owned is less. The purpose of this research is to know what factors happened in internal political party especially related to applying of regeneration function and political recruitment and candidate procession in all parties so that only one pair of candidates appeared. The method used is qualitative descriptive by conducting interviews to all political parties in Pati Regency and also to community leaders in Pati Regency regarding their response to the phenomenon that occurred. Having studied in depth the single candidate that occurred in Pati district because the figure of Haryanto who is a incumbent is very strong and has a high level of elektability. While Saiful Arifin figure who is a businessman is considered strong economically. So that the political parties in Pati Regency feel there are no one member who are able to compete with Haryanto-Arifin the stong pair both politically and economically. The emergence of a pair of candidates has triggered a group of people trying to win empty boxes in the hope of a repeat election in 2018 so that potential other figures can emerge. The process of regeneration and political recruitment inherent in the main function of political parties should be able to produce politically powerful figures. But in Pati Regency all parties seemed to not perform its functions optimally because the party does not believe the potential of cadres and the power of his own party machine. Pilkada which was only followed by a pair of candidates who had to fight empty boxes became an unfeasible democratic contestation. Keywords: Pilkada 2017, Singgle Pair Candidate, Empty Box, Regeneration and Political Recruitment